A deep look into thin melanomas: What's new for the clinician and the impact on the patient - A.J. Chiaravalloti, MD; S. Jinna, MD; P.E. Kerr, MD; J. Whalen, MD; J.M. Grant-Kels, MD (Wolters Kluwer, 2018)
Melanoma incidence and mortality are on the rise and although most new cases of melanoma are thin, a significant percentage of these patients still experience disease progression. The American Joint Committee on Cancer publishes staging criteria for melanoma, which were recently updated to the 8th edition. The most significant revision from the 7th edition affects the T1b classification, which now includes melanomas with a Breslow depth of 0.8 mm to 1.0 mm. The second major revision eliminates mitoses as a criterion to upstage a thin melanoma to T1b. Although mitotic figures have been established as an independent prognostic factor, they do not have a significant correlation with sentinel lymph node (SLN) biopsy positivity. SLN status remains the most important independent prognostic factor in thin melanomas. Nonetheless, the identification of patients who are at the highest risk for having a positive SLN test result remains difficult. Importantly, a positive SLN test result has high positive predictive value, but a negative one has very low negative predictive value. Since there is no proven survival benefit in performing an SLN biopsy in T1 disease, dermatologists need to have a personalized discussion with patients with thin melanomas to review expected risks and benefits before undertaking this procedure. Keywords: melanoma, thin melanomas, AJCC 8th edition, sentinel lymph node biopsy